2020
DOI: 10.31100/dikdas.v3i2.666
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Komik Berbasis Digital Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Metamorfosis Di Kelas Tinggi

Abstract: This study aims to develop digital-based comic media on students' critical thinking skills on high-class metamorphosis material. This type of research uses Research and Development (RnD). The research instrument used questionnaires and tests. The subject of this research was conducted by a validator (a media expert lecturer, a material expert lecturer and 2 homeroom teachers). It can be concluded that the quality of comic products as a learning medium for critical thinking skills based on validation results by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Other studies are not much different. (Andayani et al, 2020;Azizul et al, 2020;Harmawati et al, 2020;Kurniawati & Koeswanti, 2021;Ratnasari & Ginanjar, 2020;Sukmanasa et al, 2017) It also showed that the development of digital comics gets good to very good qualifications with high scores. The results obtained are related to the characteristics of the comic itself, which is the arrangement of ordered pictures and storytelling, which is an interesting thing for elementary school students.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies are not much different. (Andayani et al, 2020;Azizul et al, 2020;Harmawati et al, 2020;Kurniawati & Koeswanti, 2021;Ratnasari & Ginanjar, 2020;Sukmanasa et al, 2017) It also showed that the development of digital comics gets good to very good qualifications with high scores. The results obtained are related to the characteristics of the comic itself, which is the arrangement of ordered pictures and storytelling, which is an interesting thing for elementary school students.…”
Section: Discussionmentioning
confidence: 93%
“…Development of comics for motion teaching materials with the percentage of validity of material experts 76.89% with a decent category and media experts with 89.17% with a very good category (Azizul et al, 2020). The development of digital-based comic media towards students' critical thinking skills on metamorphosis material in high class is very well qualified from the validity test of material experts and practitioners (Andayani et al, 2020). The development of digital comics as an educational medium for natural disaster management has received qualifications from both material experts and practitioners (Ratnasari & Ginanjar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research on comic development that aims to improve critical thinking skills has been carried out by Andayani et al (2020) to increase the critical thinking competence of elementary school students. The research conducted was not on mathematics subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Digital comics contain images, animations, and sounds that can accommodate students to interpret abstract material in more concrete (Aulia & Dewi, 2021;Ayu, Pinatih, Kt, & Semara, 2021). The advantage of developing digital comics is that learning activities will become more interesting and not monotonous (Andayani, Maula, & Sutisnawati, 2020;Kanti, Suyadi, & Hartanto, 2018). It is because students not only learn to use illustrated texts, but students learn through moving pictures and are also equipped with audio in digital comics to provide a learning experience that is difficult to learn directly (Suprianto, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using digital comic media in learning can increase students' knowledge about good morals (Khoerunajah, Fadhilah, Novita, & Aeni, 2022). Other research shows that the development of digital comic media is valid and feasible to use in the learning process (Andayani et al, 2020;Wahid, Mutaqin, & Yasin, 2021). Based on this opinion, it can be said that digital comic media can increase students' motivation to learn so that it is feasible to use.…”
Section: Introductionmentioning
confidence: 99%